Protein-Based Vaccine Protect Against Piscirickettsia salmonis in Atlantic Salmon (Salmo salar) - Pontigo, Juan Pablo; Espinoza, Carla; Hernandez, Mauricio; Nourdin, Guillermo; Oliver, Cristian; Avendaño-Herrera, Rubén; Figueroa, Jaime; Rauch, Cecilia; Troncoso, José M.; Vargas-Chacoff, Luis; Yáñez, Alejandro J. (Frontiers in Immunology, 2021)
An effective and economical vaccine against the Piscirickettsia salmonis pathogen is needed for sustainable salmon farming and to reduce disease-related economic losses. Consequently, the aquaculture industry urgently needs to investigate efficient prophylactic measures. Three protein-based vaccine prototypes against Piscirickettsia salmonis were prepared from a highly pathogenic Chilean isolate. Only one vaccine effectively protected Atlantic salmon (Salmo salar), in correlation with the induction of Piscirickettsia-specific IgM antibodies and a high induction of transcripts encoding pro-inflammatory cytokines (i.e. Il-1β and TNF-α). In addition, we studied the proteome fraction protein of P. salmonis strain Austral-005 using multidimensional protein identification technology. The analyzes identified 87 proteins of different subcellular origins, such as the cytoplasmic and membrane compartment, where many of them have virulence functions. The other two prototypes activated only the innate immune responses, but did not protect Salmo salar against Piscirickettsia salmonis. These results suggest that the knowledge of the formulation of vaccines based on P. salmonis proteins is useful as an effective therapy, this demonstrates the importance of the different research tools to improve the study of the different immune responses, resistance to diseases in the Atlantic salmon. We suggest that this vaccine can help prevent widespread infection by P. salmonis, in addition to being able to be used as a booster after a primary vaccine to maintain high levels of circulating protective antibodies, greatly helping to reduce the economic losses caused by the pathogen.